Not Just Holidays. The Social and Symbolic Significance of Summer Returns for Tunisian Descendants - Calabretta, Andrea (Italian Sociological Review, 2025)
Sayad describes migrants’ holidays in their country of origin as a pathology that highlights the contradictions of migration (2001), from the guilt of emigration to the mutual accusations between migrants and non-migrants (Sayad, 1999a). Hence, it is interesting to look at summer returns from the perspective of the ‘illegitimate children’ of migration, that is migrants’ descendants (Sayad, 1979a, 1979b), who are characterised by an even more ‘ambiguous’ positioning between the society of immigration and that of emigration than their parents (Sayad, 1994). Based on these premises, this paper examines the summer return experiences of 35 migrants’ descendants, focusing on their relationship with native peers and families of origin and analysing their representations of their home country. It draws on qualitative interviews conducted in 2020–2021 with Tunisian descendants who grew up in Northern and Southern Italy. Inspired by Sayad’s insights, this paper uses the holidays of migrants’ descendants in Tunisia as a means to explore their positioning in symbolic struggles and social hierarchies, both in their country of origin and in Italy. Rejecting the idea of a ‘homogeneous’ migration (Sayad, 1977), the paper links the diverging holiday experiences of research participants to different ways of ‘integrating’ into both societies, reaffirming the continuity of the emigration-immigration nexus.